2012
DOI: 10.1637/9831-061311-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Astroviruses as Causative Agents of Poultry Enteritis: Genetic Characterization and Longitudinal Studies on Field Conditions

Abstract: Astroviruses (AstVs) are nonenveloped RNA small round viruses (SRVs) with a genome of 6.8-7.9 kb. Known avian AstVs are spread worldwide; they have been associated with poult enteritis and mortality syndrome in the United States and reported in Italy in intensive turkey and guinea fowl flocks. Nevertheless, their real prevalence and their pathogenic role in avian enteritis affecting Italian flocks is far from clear. Negative staining electron microscopy (nsEM) is used for the routine diagnosis of avian enteric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 9 publications
3
10
0
1
Order By: Relevance
“…Our observations of varying levels of nt and aa identities of ANV compared with previously published polymerase gene sequences of ANV from abroad are consistent with the earlier reports (Canelli et al, 2012;Kang et al, 2012). Phylogenetic analysis revealed that all ANVs of this study clustered together.…”
Section: Discussionsupporting
confidence: 92%
“…Our observations of varying levels of nt and aa identities of ANV compared with previously published polymerase gene sequences of ANV from abroad are consistent with the earlier reports (Canelli et al, 2012;Kang et al, 2012). Phylogenetic analysis revealed that all ANVs of this study clustered together.…”
Section: Discussionsupporting
confidence: 92%
“…However, later on, two genera were established based on their hosts of origin: Mamastrovirus (MAstV) and Avastrovirus (AAstV), infecting mammalian and avian species, respectively. Although initially detected in children's stool, AstVs have been found in the feces of a wide variety of mammalian species, i.e., cats (6), cattle (7), deer (8), dogs (9), mice (10), rats (11), pigs (12), sheep (13), mink (14), bats (15), cheetahs (16), rabbits (17), and even sea lions and dolphins (18), as well as in avian species, i.e., turkeys (19), chickens (20), ducks (21), pigeons (22), and guinea fowl (23) and other wild aquatic birds (24).…”
mentioning
confidence: 99%
“…To better characterize and identify those particles observed using ns-EM methods that were morphologically classified as small round viruses (SRVs), AstVs and enterovirus-like viruses (ELVs), we further analyzed samples of different avian commercial species, including turkey, with RT-PCR targeting the open reading frame (ORF)-1b of AstV, which encodes an RNA-dependent polymerase. We then sequenced and genetically analyzed the RT-PCR positive samples, and we performed a phylogenetic analysis to distinguish and type them [ 37 ]. This study also permitted us to compare the results obtained by the two diagnostic methods (RT-PCR vs .…”
Section: Resultsmentioning
confidence: 99%